MANAGERS AND MANAGEMENT ON INDUSTRY AND CONSTRUCTION BUSINESSES IN THE REGION OF VALE DO SOUSA - Francisco Diniz; Nelson Duarte (European Regional Science Association (ERSA), 2011)
This article goal is to analyse firms and manages behaviour on a Portuguese region on construction and industry businesses. The results are based on 251 questionnaires. Usually managers present a low level of school education (changing recently). On what regards management issues it was realized that the main reason for business choice is the past experience of firm owners, and they started their businesses at their own homes (embeddedness?). The strategies followed by these firms reveal a risk adversity attitude and a lack of cooperation, considering their neighbours competitors instead of potential business partners. As a general conclusion it can be realized that in general these firms are not fostering local development.
Keywords: 330